2021
DOI: 10.5624/isd.20200259
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of occlusal incipient caries in the visible and near-infrared range

Abstract: Purpose This study aimed to demonstrate the presence of dental caries through a photoacoustic imaging system with visible and near-infrared wavelengths, highlighting the differences between the 2 spectral regions. The depth at which carious tissue could be detected was also verified. Materials and Methods Fifteen permanent molars were selected and classified as being sound or having incipient or advanced caries by visual inspection, radiography, and optical coherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…28 This technique can image soft tissue and does not utilize ionizing radiation. 12,20,29 The anatomical area and extension of periodontal tissue inflammation can be determined based on acoustic intensity acquired from PA imaging.…”
Section: Discussionmentioning
confidence: 99%
“…28 This technique can image soft tissue and does not utilize ionizing radiation. 12,20,29 The anatomical area and extension of periodontal tissue inflammation can be determined based on acoustic intensity acquired from PA imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Silva et al demonstrated PAI of occlusal incipient caries [178]. It was proved that a higher intensity of the PA signal could be observed in regions with lesions, while healthy surfaces showed much less PA signal (Figure 23).…”
Section: Whole Body (Deep Tissue) Imagingmentioning
confidence: 92%
“…The applications of PAI in dentistry started in 2006 [76] and have since been used in studies of caries diagnostics, periodontology, dental implants and blood detection in dental pulp [77][78][79][80][81][82]. Due to the already described difficulties for imaging approaches to detect occlusal caries, besides OCT with the aid of OCA described before, we employed PAI, and more specifically PAM, to image occlusal caries [83]. The results of ref.…”
Section: Pai: From Basics To Nanodentistry Applicationsmentioning
confidence: 99%
“…The results of ref. [83] are shown in Figure 10. Part A shows the experimental setup, which employed a Q-switched Nd:YAG laser with selective wavelengths of 532 nm and 1064 nm, a pulse width of 6 ns, and a repetition rate of 10 Hz.…”
Section: Pai: From Basics To Nanodentistry Applicationsmentioning
confidence: 99%